2023
DOI: 10.1038/s41598-023-28354-0
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of soybean cultivars to drought stress during flowering and early-seed setting stages

Abstract: Drought stress during the reproductive stage and declining soybean yield potential raise concerns about yield loss and economic return. In this study, ten cultivars were characterized for 20 traits to identify reproductive stage (R1–R6) drought-tolerant soybean. Drought stress resulted in a marked reduction (17%) in pollen germination. The reduced stomatal conductance coupled with high canopy temperature resulted in reduced seed number (45%) and seed weight (35%). Drought stress followed by rehydration increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Similarly, Poudel et al. 's (2023) study showed greater yields at optimum irrigation conditions as compared to suboptimal conditions. According to USDA‐NASS (2022), the average soybean yield in Mississippi was 3631 kg ha −1 (rainfed) and 4000 kg ha −1 (irrigated); our results under irrigated scenario are comparable to the Mississippi average yields.…”
Section: Resultsmentioning
confidence: 79%
“…Similarly, Poudel et al. 's (2023) study showed greater yields at optimum irrigation conditions as compared to suboptimal conditions. According to USDA‐NASS (2022), the average soybean yield in Mississippi was 3631 kg ha −1 (rainfed) and 4000 kg ha −1 (irrigated); our results under irrigated scenario are comparable to the Mississippi average yields.…”
Section: Resultsmentioning
confidence: 79%
“…The negative effect of drought on pollen germination was confirmed in multiple crops, e.g. in maize (Zea mays L.) (Bheemanahalli et al, 2022), soybean (Glycine max) (Poudel et al, 2023), and rice (Oryza sativa) (Rao et al, 2019). We did not measure precipitation at the sites, but data from a drought monitoring project by the Global Change Research Institute of the Czech Academy of Sciences (https://www.intersucho.cz/) show that the area where the highland sites were located consistently has higher soil water content than the lowland area, including during the time of our sampling.…”
Section: Discussionmentioning
confidence: 95%
“…For the yield parameters, cultivars 44-D49 were tolerant under drought and heat stress (Figure 6c). However, the cultivar DM45X61, which performed better in terms of physiology under individual heat and drought, did not show the highest rank for yield, possibly due to the negative impacts of the stress on the pollen viability and reproductive failure (Bheemanahalli et al, 2019;Poudel et al, 2023b). Meanwhile, under combined stress, the cultivar G4620RX, with the highest tolerance for physiological performance, showed better ranking for yield parameters (Figure 6a).…”
Section: Stress Tolerance Indexmentioning
confidence: 99%
“…Exposure of soybean cultivars to drought stress during the reproductive and seed filling decreased seed number and weight (Poudel et al, 2023b). These decreases were associated with reduced stomatal conductance and increased canopy temperature under drought.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation